2019
DOI: 10.1108/ijshe-02-2019-0064
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of sustainability education in nursing

Abstract: PurposeThe purpose of this study was to assess the contribution of scenario-based learning aimed at raising awareness of sustainability in healthcare practitioners. The Lancet Countdown on Climate Change calls for urgent action on health and climate change;; this requires appropriate knowledge, skills and competencies that can be gained through undergraduate education. The International Council of Nurses calls for leadership in nursing for sustainability, however climate change and health are given little atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…These results demonstrated an improvement in competencies, attitudes, knowledge and skills in children environmental health issues. The findings are similar to those found by Richardson et al [8,10,30] and Grose et al [31] in skills sessions with nursing students in the United Kingdom but they differ from those found by Richardson et al [32] which revealed no statistical differences, however, this could possibly be explained by their small sample size. In Richardson et al [30,32], SANS and SANS_2 were used respectively to assess the skills gained in a session related to sustainability three months after the intervention, so comparisons can be made.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results demonstrated an improvement in competencies, attitudes, knowledge and skills in children environmental health issues. The findings are similar to those found by Richardson et al [8,10,30] and Grose et al [31] in skills sessions with nursing students in the United Kingdom but they differ from those found by Richardson et al [32] which revealed no statistical differences, however, this could possibly be explained by their small sample size. In Richardson et al [30,32], SANS and SANS_2 were used respectively to assess the skills gained in a session related to sustainability three months after the intervention, so comparisons can be made.…”
Section: Discussionsupporting
confidence: 87%
“…The World Health Organization (WHO) estimates that approximately one-third of the disease burden in developing countries can be attributed to modifiable environmental factors, including indoor and outdoor air pollution, unsafe water, inadequate sanitation, and poor hygiene. The Lancet Countdown on Climate Change and the International Council of Nurses have recommended the integration of environmental health into nursing practice, education, research and policy/advocacy work [8]. Therefore, health professionals have an important role to play in understanding and communicating environmental-health-related issues to children and their families.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second‐year session was delivered alongside clinical skills practice and was based on an interruption to supply of important healthcare products and challenges to the sustainable disposal of clinical waste (Grose & Richardson, 2013a, 2013b). Previous studies, based on more than 600 students, demonstrated significant changes in knowledge and attitudes toward sustainability and climate change following this particular session (Richardson et al, 2017, 2019).…”
Section: Methodsmentioning
confidence: 73%
“…A cohort study method was used to collect data on two occasions following exposure to sustainability educational interventions that were designed to be relevant to the nursing undergraduate curriculum (Richardson, Clarke, Grose, & Warwick, 2019); this report is on the inductive content analysis of open‐ended questions included in the survey.…”
Section: Methodsmentioning
confidence: 99%